The Comparison of Indonesian and American Consumer Protection Laws: What and How? - Dwi Edi Wibowo (SASI)
Introduction: In this rapidly developing era of globalization, consumer protection has become an important global issue, with consumers having the right to receive adequate protection from the government and relevant legal institutions in various aspects such as product safety, service quality, and fair transactions.